INTEGRATION OF BIM AND GIS TECHNOLOGIES IN MODERN URBAN PLANNING: CHALLENGES AND PROSPECTS (World Bulletin of Social Sciences, 2024)
This article examines the integration of BIM (Building Information Modeling) and GIS (Geographic Information Systems) within the context of contemporary urban planning challenges. Methods and results are presented, including an analysis of the key aspects of these technologies, with successful project examples such as the digital twin of Helsinki and the "Smart Cities" program in India. The benefits of integration include improved design accuracy, cost reduction, and enhanced environmental sustainability of urban environments. Additionally, recommendations for technology adoption and specialist training are proposed to facilitate the transition to more efficient and sustainable cities